The value of audio description for the therapy of speech-communicative disorders - Zabrocka, Monika (Revista de Investigación en Logopedia, 2022)
The article aims at presenting the potential of audio description (AD) as an efficient tool to support the speech-language and social-communicative skills of children with developmental disorders. It includes information for both speech therapists and parents on what they may expect from AD, and how they can use it in their everyday work with children. It may also serve as a set of guidelines for AD creators for making their products more effective. The considerations assembled in the article are based on a literature review. Remarks on the possible uses of AD are presented in the context of various problems to be remedied during speech therapy of a child; they range from incorrect articulation of sounds, through hearing problems such as auditory processing disorder, to developmental disabilities, such as autism spectrum disorder (ASD) characterized by difficulties with social interaction and repetitive behaviors including pretending play. The existing evidence proves that audiovisual (AV) materials are an attractive starting point for exercises with a child. Video-modeling, in turn, has proven to be one of the best tools for therapy of individuals with ASD, allowing for better understanding of interpersonal interactions. Therefore, AV materials accompanied with an AD track – which itself is perceived as a tool for enhancing information processing by children – need to demonstrate similar value for mastering communicative competences. AD can be an effective tool in speech therapy. However, to meet the needs of practitioners, caregivers and beneficiaries in a useful manner, it must be prepared with care regarding both its content and form.
Keywords: alternative audio description; speech therapy; developmental disorders; linguistic competences; social skills